Paysage, chemin et errance chez Julien Gracq - Ana Isabel Moniz (Carnets)
Wandering, recurrent theme in Julien Gracq’s writings, presupposes the will to seek new experiments allied to a profound will of inner change. Within the specific context of his literary creation, wandering unveils a sense of unfulfillment that leads his heroes onto the quest of and discovery of new horizons. As rupture with the past, by means of successive transgressions and continuous ordeals, aiming at a radical change of his life, wandering endangers the identity and integrity of an I that becomes diluted and is reborn transformed. In this article I will try to find one or various explanations to that need felt by Julien Gracq’s characters that induce them to constantly roam from place to place aiming at deciphering the enigma of the I in his/her relation with the world. This explains why the author makes them evolve in a constant oscillation between journeying and wandering.